Aspectos correlacionais da inteligência emocional, gratidão e autorregulação emocional - Silva, Elismar (Universidade Federal de São Carlos, 2025)
Emotional intelligence (EI) is the ability to accurately process emotional information through mental processes that involve the recognition, regulation, and adaptive application of emotions, in oneself and others. Its development is a fundamental aspect for the individual. Its organization is closely linked to emotional self-regulation, which refers to the different mental processes that exert control and influence our thoughts, feelings, and behaviors. Gratitude is a character-strength construct linked to transcendence; that is, gratitude is a feeling that responds to something we receive, whether material or not. This study aimed to analyze which aspects of emotional intelligence relate to self-regulation and gratitude. 258 people over 18 years of age, from all regions of Brazil, participated in this online survey. A strong correlation was observed between the measures of emotional regulation, as they assess the same construct from opposite perspectives. We also identified that gratitude is moderately related to better empathy, sociability, and emotional regulation. Finally, a centrality was found for QoE2, a factor that concerns cognitive empathy, which may be a facilitator for the development of other constructs.
Correlational aspects of emotional intelligence, gratitude, and emotional self-regulation
Keywords: Inteligência emocional; Autorregulação; Gratidão; Construto; CIENCIAS HUMANAS::PSICOLOGIA